Antecedents and consequences of job satisfaction among nurses in the public sector hospital in Pakistan - Qureshi, Muhammad Asif (2018)
In light of a massive shortage of registered nurses globally as well as in developing countries such as Pakistan, nurses overwhelmingly face challenges with regard to job satisfaction. This is a looming problem in the public hospitals of Pakistan. Therefore, this study analyzed the impact of four antecedents of nurses' job satisfaction. These antecedents included esprit-de-corps, supervisor support, job clarity, and work autonomy. Using a self-administered survey questionnaire, a sample of 280 responses was drawn from 43 public hospitals in four major cities of the Sindh province of Pakistan by using the multi-stage cluster sampling method. The variance-based structural equation modeling (VB-SEM) method was used in SmartPLS 3.0 to develop a measurement model for testing the hypotheses. The measurement model confirmed high construct reliability and convergent validity. Besides, discriminant validity was assessed using the Fomell-Larcker Criterion and the Heterotrait-Monotrait Ratio (HTMT) matrix. The results showed that job clarity and supervisor support do not predict nurses' job satisfaction except work autonomy. Interestingly, it was also found that perception of fairness does not play a moderating role with any of the four antecedents; rather, it serves as another very strong predictor of nurses' job satisfaction. Therefore, the management of public hospitals in Sindh should institutionalize such organizational practices which could not only increase the perception of fairness among nurses but also enhance their job satisfaction. The research findings contribute to the job satisfaction literature that the perception of fairness is a very strong predictor of job satisfaction. Hence, it should be used in future studies with other mediating or moderating variables under disparate untapped social settings.